Characterisation and modelling of PC/ABS blends - Hund, Jonas (Schriftenreihe des Instituts für Mechanik, Karlsruher Institut für Technologie, 2022)
The present work deals with the characterisation and multi-scale modelling of the large-strain response of ternary polymer blends. In a homogenised constitutive modelling approach, particularly the deformation behaviour featuring plastic dilatancy is investigated. Concerning the micromechanical modelling, constitutive models are proposed for the blends' individual phases and compared regarding their capabilities to capture the composition-dependent fracture toughness in unit cell models.